Managing and leading people through organizational change : the theory and practice of sustaining change through people - Hodges, Julie (KoganPage, 2016)
"Tremendous forces for change are radically reshaping the world of work. Disruptive innovations, radical thinking, new business models, and resource scarcity are impacting every business sector. Although the scale of expected change is not unprecedented, what is unique is the pervasive nature of the change and its accelerating pace. While structures, systems, processes, and strategies are relatively simple to understand and even fix, people are more complex. Change can have a different impact on each individual, which can cause different attitudes and reactions.Managing and Leading People through Organizational Change provides a critical analysis of change and transformation in organizations from both a theoretical and practical perspective. It addresses the individual, team, and organizational issues of leading and managing people before, during and after change, using case studies and interviews with people from organizations in different industries across the globe. Each chapter includes learning objectives, boxed summaries, diagrams/models, case examples with questions, exercises, and a list of references and further reading. "--